From waste to resource: the potential of using cassava wastewater as fertilizer in agriculture - Silva, Wemerson Leonardo Cruz da; Santos, Lourenço Oliveira dos (Brazilian Journal of Production Engineering, 2025)
Manipueira, the liquid residue from cassava processing, has high potential as a fertilizer due to its composition rich in essential nutrients (N-P-K). Its use in agriculture has been studied as a sustainable alternative to reduce reliance on chemical fertilizers and minimize environmental impacts caused by improper disposal of this waste. In this context, the objective was to analyze the main effects of using manipueira as a fertilizer, as evidenced in the scientific literature, focusing on its influence on soil fertility, plant development, and agricultural productivity. The methodology adopted for this study consisted of an Integrative Literature Review (ILR), conducted through searches in the SciELO and CAPES Periodicals Portal databases, covering publications from the period 2018 to 2024. The results indicate that manipueira can improve soil structure, increase water retention, and supply essential nutrients. However, excessive use may cause salinization in poorly drained soils. Thus, it is concluded that manipueira is a promising alternative for agroecology but requires proper management.
Keywords: Soil fertility; Agricultural sustainability; Alternative fertilization